Association between the rs2106261 polymorphism in the zinc finger homeobox 3 gene and risk of atrial fibrillation: Evidence from a PRISMA-compliant meta-analysis. Issue 49 (10th December 2021) - Wei, Yue; Wang, Lingjie; Lin, Changjian; Xie, Yun; Bao, Yangyang; Luo, Qingzhi; Zhang, Ning
Abstract: Introduction: Previous genome-wide studies have identified an association between the rs2106261 single-nucleotide polymorphism (SNP) in the zinc finger homeobox 3 (ZFHX3) gene and an increased risk of atrial fibrillation (AF). However, this association remains controversial, since conflicting results have been reported in previous studies. We aimed to investigate the association between the ZFHX3 rs2106261 polymorphism and susceptibility to AF. Methods: A comprehensive literature search, of articles written in either English or Chinese, was conducted on various databases, including PubMed, Embase, Web of Science, the Cochrane library, Wan Fang, and CNKI, for studies performed up to August 1, 2020. Data were abstracted and pooled using Stata 14.0 software. A meta-analysis was performed on all selected studies based on ZFHX3 rs2106261 polymorphism genotypes. Results: Nine studies, including 10, 107 cases and 58, 663 controls, were analyzed in the meta-analysis. In the overall population, a significant association was found between AF and the T-allelic ZFHX 3 rs2106261 SNP (odds ratio [OR] = 1.32, 95% confidence interval [CI] 1.19–1.46). In subgroup analysis, a significant association between the T-allele of rs7193343 and risk of AF in Caucasian (OR = 1.23, 95% CI 1.10–1.37) and Asian subgroups (OR = 1.58, 95% CI 1.32–1.89) was observed. However, no statistically significant association was found in African populations (OR = 1.06, 95% CI 0.95–1.19). Conclusion: The genetic variant rs2106261 SNP is associated with susceptibility to AF in Caucasian and Asian individuals, with Asian samples showing a stronger association. However, based on the current evidence, no association was found in African samples. Future studies, with larger sample sizes and multiple ethnicities, are still necessary. Abstract : Supplemental Digital Content is available in the text